Perubahan dan Keberlanjutan Tradisi di Puri Saren Agung Ubud: Perkembangan Tradisi dari Masa ke Masa - Fisabilillah, Aqillah; Febriyanti, Delima; Septianingrum, Eka Lutviana; Nadiya Vianney; Khoiruddin, Muhammad Mu'ammar; Maulidiya, Gita; Virgiawan, Dhimas Bagus; Khotimah, Kusnul (Program Studi Pendidikan Sejarah - Universitas Samudra, 2025)
This study aims to analyze the transformation and continuity of traditions at Puri Saren Agung Ubud as a response to social, cultural, and temporal dynamics. More than a symbol of traditional authority, the Puri functions as a center for spiritual and cultural activities in Balinese society. Using a qualitative approach with historiographical methods, data were collected through in-depth interviews and literature review. The findings reveal that traditional practices such as religious ceremonies and performing arts have shifted in function—from sacred rituals to public cultural attractions. However, the core values embedded in these traditions are still preserved and passed down through generations. This transformation is driven by two main factors: government policies promoting cultural tourism and the active involvement of the younger generation, who utilize digital platforms to preserve ancestral heritage. Preservation strategies include direct value transmission, the functional use of traditional spaces, and collaboration between royal family members and local communities. The study concludes that tradition at Puri Saren Agung remains rooted in local identity while demonstrating a high capacity for adaptation. The Puri successfully blends cultural preservation with innovation, serving as a compelling example of how traditional practices can endure and remain relevant in the modern era.